Factors influencing seasonal anestrus in buffaloes and strategies to overcome the summer anestrus in buffaloes - Kennady, Vijayalakshmy; Verma, Ranjeet; Rahman, Habibar; Yadav, Hanuman; Virmani, Meenakshi; Kumar, Dharmendra; Choudhiry, Vikas (Informa UK Limited, 2020)
Reproductive managements of buffalo during the summer season a challenging task livestock’s owner. There are different factors contributes to this condition; the most important are consequence of increased temperature and humidity that result in a decreased expression of overt sings of estrus and reduction in appetite and dry matter intake. The failure to express the overt signs of estrus is due to aberration in endocrine profile. Heat stress during the summer causes hyper-prolactinaemia, suppressing the secretion of gonadotropins, which alters the ovarian steroidogenesis. It also affects folliculogenesis, follicular fluid microenvironment and oocyte quality. A large number of hormonal regimens have been used with varying degree of efficacy in terms of estrus induction and conception rate. A combined strategy of improvement in environment, nutrition and management is pre-requisite for hormonal manipulation in order to improve productivity of buffaloes during the summer season.